Is there a Transfer “Penalty” in Ontario PSE? Insights from an Administrative Linkage - Pizarro Milian, Roger; Reynolds, Dylan; Einmann, Trisha; Walters, David; Brown, Robert; Parekh, Gillian (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Studies have explored the relationship between travelling non-linear post-secondary (PSE) pathways and student achievement in multiple jurisdictions. This research aims to overcome some of the major challenges faced by scholars in this area by leveraging a new administrative linkage in Ontario, Canada containing detailed information on students’ academic performance at the high school level, while also holistically capturing their subsequent trajectories through PSE. Our analyses allow us to estimate the presence of a transfer penalty with respect to graduation rates that survives all available controls. We discuss the implications of this penalty for both future research and policy making in Ontario and comparable jurisdictions.